"I don't know if this is right … but this is what I'm offering": healthcare provider knowledge, practice, and attitudes towards safer conception for HIV-affected couples in the context of Southern African guidelines. Issue 3 (3rd March 2016) - West, Nora; Schwartz, Sheree; Phofa, Rebecca; Yende, Nompumelelo; Bassett, Jean; Sanne, Ian; Van Rie, Annelies
ABSTRACT: The 2011 guidelines for safer conception for HIV-affected individuals and couples were adopted by the South African Department of Health in December 2012. We assessed implementation gaps and facilitators and barriers to delivering safer conception services through examining patient and healthcare provider (HCP) experiences. At Witkoppen Health and Welfare Centre, a primary care clinic in Johannesburg, we conducted in-depth interviews (IDIs) with nine HCPs (doctors, nurses, and counselors) and IDIs and focus group discussions with 42 HIV-affected men and women interested in having a child. Data were analyzed using a grounded theory approach. HCPs were supportive of fertility intentions of HIV-affected couples and demonstrated some knowledge of safer conception methods, especially ART initiation to suppress viral load in infected partners. Unfortunately, HCPs did not follow the key recommendation that HCPs initiate conversations on fertility intentions with HIV-affected men and women. Providers and clients reported that conversations about conception only occur when client-initiated, placing the onus on HIV-affected individuals. Important barriers underlying this were the misconception held by some HCPs that uninfected partners in serodiscordant partnerships are "latently" infected and the desire by most HCPs to protect or control knowledge around fertility and safer conception methods out of concern over what clients will do with this knowledge before they are virally suppressed or ready to conceive. Almost all participants who had conceived or attempted conception did so without safer conception methods knowledge. HCP concern over conception readiness, perception of what clients will do with safer conception knowledge, and gaps in safer conception knowledge prevent HCPs from initiating conversations with HIV-affected patients on the issue of childbearing. Examining these findings in the context of existing South African guidelines illuminates areas that need to be addressed to facilitate implementation of the guidelines.